Irrigação com PVP-I em baixa concentração reduz os eventos inflamatórios após cirurgia de 3˚ molares inferiores? Um ensaio clínico randomizado, triplo cego, placebo-controlado - Nogueira, Carlos Bruno Pinheiro (2016)
Purpose: This study aimed to evaluate the effect of irrigation on surgical wounds resulting from the extraction of inferior third molars, with a PVP-I formulation, on inflammatory events. Materials and Methods: A randomized, triple-blind, split-mouth, placebo-controlled clinical trial was conducted in patients undergoing inferior third molars extractions. All volunteers were randomly allocated to receive as an irrigating substance of PVP-I 0.5mg/ml or of SF 0.9% to assess inflammatory events. An estimated sample of 30 surgical sites per group was required (80% statistical power and 95% confidence level). Results: The mean duration of the procedures was 12.48 minutes. There was no statistically significant difference in pain (p = 0.352) and facial edema (p = 0.830), on the other hand for trismus in D02 PVP-I 0.5 mg/ml had a significant difference (p = 0.039), there was one significant inverse correlation in D07, demonstrating that surgery time in saline solution was crucial to reduce trismus. Conclusion: PVP-I was not significantly better for edema and pain, showing a significant improvement for trismus. Contradictory results for the different inflammatory events in the present study, makes us to believe in the need for more controlled clinical studies using the same methodology and with a larger sample in order to clarify these differences.